Doping in sport and exercise: anabolic, ergogenic, health and clinical issues. (March 2016) - Bird, Stephen R; Goebel, Catrin; Burke, Louise M; Greaves, Ronda F
The use of doping agents is evident within competitive sport in senior and junior age groups, where they are taken by non-elite as well as elite participants. They are also taken in non-sporting contexts by individuals seeking to 'improve' their physique through an increase in muscle and/or decrease in fat mass. While attaining accurate data on the prevalence of their use has limitations, studies suggest the illicit use of doping agents by athletes and non-athletes may be 1–5% in the population and greater than 50% in some groups; with the prevalence being higher in males. There is conclusive evidence that some doping agents are anabolic and ergogenic. There is also evidence that the use of doping agents such as anabolic androgenic steroids, growth hormone and other anabolic agents, erythropoietin and stimulants conveys considerable health risks that include, but are not limited to: cardiovascular disease, diabetes, cancer, mental health issues, virilisation in females and the suppression of naturally produced androgens in males. This review will outline the anabolic, ergogenic and health impacts of selected doping agents and methods that may be used in both the sporting and physique development contexts. It also provides a brief tabulated overview of the history of doping and how doping agents may impact upon the analyses of clinical samples.